Effective psychotherapists clinical skills that improve client outcomes - Miller, William R. 1947-; Moyers, Theresa B. (The Guilford Press, 2021)
Cover -- Half Title Page -- Title Page -- Copyright -- Dedication -- About the Authors -- Preface -- Contents -- Part I. Helping Relationships -- 1. An Invitation -- 2. Therapist Effects -- Part II. Therapeutic Skills -- 3. Accurate Empathy -- 4. Acceptance -- 5. Positive Regard -- 6. Genuineness -- 7. Focus -- 8. Hope -- 9. Evocation -- 10. Offering Information and Advice -- 11. The Far Side of Complexity -- Part III. Learning, Training, and Clinical Science -- 12. Developing Expertise -- 13. Teaching Therapeutic Skills -- 14. Toward a Broader Clinical Science -- References -- Index